Perkembangan Pelayanan Kesehatan Militer-Sipil dari Potret Rumah Sakit Fort de Kock (Bukittinggi) tahun 1857-1942 - Yani, Wahyu Suri (Masyarakat Sejarawan Indonesia, 2020)
This study focuses on the portrait of the Fort de Kock hospital that has changed from time to time. The process of identifying changes in paintings and photographs illustrates the development of shapes, increasing numbers, different situations of objects and portraits of military and civil society groups around the hospital building. This paper will explain the physical changes and the existence of indegenious around the hospital, in line with the changes in health services of the Dutch colonial government, initially limited for military, then since the 1920s began to be open to population in Fort de Kock. Historical research into the portrait of the Fort de Kock hospital provides an explanation the journey a century existence of health services by the Dutch colonial government in Fort de Kock as the second most important city in Sumatra Westkust.